2017
DOI: 10.3851/imp3085
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Abbott RealTime HCV and Roche COBAS Ampliprep/COBAS TaqMan HCV Assays for the Monitoring of Sofosbuvir-Based Therapy

Abstract: Over 10% of the patients continued to have detectable HCV RNA by ART at EOT, irrespective of HCV genotype, prior treatment-experience and/or cirrhosis. However, prolonged residual HCV RNA was not associated with treatment failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…Subsequent studies reported that W4VLs were undetectable in only 10%‐14% using the Abbot assay and 51%‐55% using the Roche assay among genotype 1‐infected patients treated with SMV+SOF±RIBA or daclatasvir+SOF, which is closer to our finding of 23.5% (Abbott) and 39.4% (Roche) undetectable W4VL. Taken together with these studies, our findings suggest that DAQ and DBQ at W4VL is a common occurrence that merits further study, and that it is much more common with the Abbott than with the Roche assays, as demonstrated by two other recent studies . Whether the higher positivity rate of the Abbott relative to the Roche assay is due to a greater true‐positive rate or a greater false‐positive rate or both remains to be determined.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Subsequent studies reported that W4VLs were undetectable in only 10%‐14% using the Abbot assay and 51%‐55% using the Roche assay among genotype 1‐infected patients treated with SMV+SOF±RIBA or daclatasvir+SOF, which is closer to our finding of 23.5% (Abbott) and 39.4% (Roche) undetectable W4VL. Taken together with these studies, our findings suggest that DAQ and DBQ at W4VL is a common occurrence that merits further study, and that it is much more common with the Abbott than with the Roche assays, as demonstrated by two other recent studies . Whether the higher positivity rate of the Abbott relative to the Roche assay is due to a greater true‐positive rate or a greater false‐positive rate or both remains to be determined.…”
Section: Discussionsupporting
confidence: 76%
“…Taken together with these studies, our findings suggest that DAQ and DBQ at W4VL is a common occurrence that merits further study, and that it is much more common with the Abbott than with the Roche assays, as demonstrated by two other recent studies. 23,24 Whether the higher positivity rate of the Abbott relative to the Roche assay is due to a greater true-positive rate or a greater false-positive rate or both remains to be determined. Many baseline characteristics that are negative predictors of SVR were also found to be predictors of positive W4VL as might be expected, such as genotype 3 HCV, baseline viral load >6 million IU/mL, Black race, cirrhosis, low platelet count and other laboratory markers of liver dysfunction.…”
Section: Sustained Virologic Response In Patients With Genotype 1 Hmentioning
confidence: 99%
“…On the contrary no patient infected with HCV GT2 or GT3 obtained an EOT DNQ by the Roche Taqman assay. In our clinical setting and across a panel of different genotypes and clinical conditions, we were able to confirm the findings of around 30% of W4 DNQ samples by ART and around 10% at EOT . These figures are definitely lower when the Roche Taqman HPS Assay for HCV RNA quantification is used, instead of the ART .…”
Section: Discussionsupporting
confidence: 72%
“…12 It was reported that HCV kinetics differed, between the COBAS AmpliPrep/COBAS TaqMan HCV test used in this study and the Abbott Real-time HCV test (ART, Abbott Diagnostics, Lake Forest, IL, USA). 13,14 In conclusion, the reduction in serum HCV-RNA levels 1 day after the start of anti-HCV IFN-free regimens with DAAs was not correlated with any patient characteristics except for liver fibrosis. This reduction was associated with virologic outcomes in patients receiving 12-week regimens and was predictive of SVR and is thus a potential factor for identifying patients at risk of treatment failure.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, differences between assays for HCV‐RNA quantification need to be considered . It was reported that HCV kinetics differed, between the COBAS AmpliPrep/COBAS TaqMan HCV test used in this study and the Abbott Real‐time HCV test (ART, Abbott Diagnostics, Lake Forest, IL, USA) …”
Section: Discussionmentioning
confidence: 99%